Penerapan Prinsip Keadilan Dalam Pertanggungjawaban Hukum Pejabat Pembuat Akta Tanah (PPAT) Atas Pembatalan Akta Hibah Oleh Pengadilan - Razaq, Abdu; Susilawati, Susi; Miqat, Nurul; Crystalia, Mega (LPPM Institut Pendidikan Nusantara Global, 2025)
This study aims to analyze the application of the principle of justice in the legal accountability of Land Deed Officials (PPAT) concerning the annulment of deed of gift (hibah) by courts in Indonesia. The increasing number of annulments of gift deeds by the Supreme Court reflects a tension between the legal certainty of authentic deeds and substantive justice for the parties involved, particularly the heirs. This research employs a normative juridical method with a statutory, conceptual, and case approach. Data were collected through library research on primary legal materials such as legislation and court decisions, as well as secondary legal materials including books, journals, and expert opinions. The analysis was conducted qualitatively using a deductive method to interpret land law norms within the concrete cases of deed annulment. The findings reveal that the application of Aristotle’s distributive and corrective justice principles serves as the foundation for assessing the validity and fairness of gift deeds. Courts may annul formally valid deeds if they are proven to violate the principle of proportionality and harm the heirs’ rights, affirming that substantive justice prevails over administrative certainty. In this context, PPATs are not merely administrative officials but also act as guardians of substantive justice in land law practices. The study underscores the need for policy reform and the strengthening of PPAT professional ethics to ensure that deed-making procedures consider moral and social aspects of justice. Further research is recommended to adopt an empirical approach to evaluate public perceptions of justice in gift and land practices.